2020
DOI: 10.3389/fgene.2020.567630
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-coding RNA LINC00115 Contributes to the Progression of Colorectal Cancer by Targeting miR-489-3p via the PI3K/AKT/mTOR Pathway

Abstract: Long non-coding RNAs (lncRNAs) are tumor-related regulators and have been found to be involved in the underlying molecular mechanisms of colorectal cancer (CRC). However, the role of lncRNA LINC00115 during CRC progression is not entirely elucidated. In this study, we discovered that LINC00115 was significantly overexpressed in CRC, and its overexpression predicted poor patient outcomes. Downregulation of LINC00115 markedly inhibited CRC cell proliferation, increased cell apoptosis, and suppressed cell migrati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 34 publications
3
19
1
Order By: Relevance
“…Chen et al (2017) reported that DLEU2 downregulates miR-30a-5p, resulting in poor prognosis in patients with ccRCC. LINC00115 can target miR-489-3p through the PI3K/AKT/mTOR pathway to promote the progression of colorectal cancer (Feng et al, 2020), and it can be activated by TGF-β to regulate the tumorigenicity of glioblastoma (Tang et al, 2019). Zhu et al (2020) reported that lncRNA SNHG10 contributes to the proliferation and invasion of osteosarcoma by activating Wnt/β-catenin signaling via sponging miR-182-5p.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al (2017) reported that DLEU2 downregulates miR-30a-5p, resulting in poor prognosis in patients with ccRCC. LINC00115 can target miR-489-3p through the PI3K/AKT/mTOR pathway to promote the progression of colorectal cancer (Feng et al, 2020), and it can be activated by TGF-β to regulate the tumorigenicity of glioblastoma (Tang et al, 2019). Zhu et al (2020) reported that lncRNA SNHG10 contributes to the proliferation and invasion of osteosarcoma by activating Wnt/β-catenin signaling via sponging miR-182-5p.…”
Section: Discussionmentioning
confidence: 99%
“… 19 A recent study reported that LNC00115 expression was markedly elevated in colorectal cancer, and LNC00115 was shown to increase the expression of mTOR by inhibiting miR-489-3p expression to promote cell proliferation and migration. 20 However, its role in ovarian cancer is still unknown. In this study, we confirmed for the first time that LNC00115 is closely related to ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…A publicly available bioinformatic database Starbase v.2.0 ( 15 ) was utilized to predict the downstream microRNAs of circRNA-100395.…”
Section: Methodsmentioning
confidence: 99%